Stabilization of the SNARE Core by Complexin-1 Facilitates Fusion Pore Expansion - Pierson, Josh; Shin, Yeon-Kyun (Frontiers in Molecular Biosciences, 2021)
In the neuron, neurotransmitter release is an essential function that must be both consistent and tightly regulated. The continuity of neurotransmitter release is dependent in large part on vesicle recycling. However, the protein factors that dictate the vesicle recycling pathway are elusive. Here, we use a single vesicle-to-supported bilayer fusion assay to investigate complexin-1 (cpx1)’s influence on SNARE-dependent fusion pore expansion. With total internal reflection (TIR) microscopy using a 10 kDa polymer fluorescence probe, we are able to detect the presence of large fusion pores. With cpx1, however, we observe a significant increase of the probability of the formation of large fusion pores. The domain deletion analysis reveals that the SNARE-binding core domain of cpx1 is mainly responsible for its ability to promote the fusion pore expansion. In addition, the results show that cpx1 helps the pore to expand larger, which results in faster release of the polymer probe. Thus, the results demonstrate a reciprocal relationship between event duration and the size of the fusion pore. Based on the data, a hypothetical mechanistic model can be deduced. In this mechanistic model, the cpx1 binding stabilizes the four-helix bundle structure of the SNARE core throughout the fusion pore expansion, whereby the highly curved bilayer within the fusion pore is stabilized by the SNARE pins.